Screen Seen Dance Screen Brighton - McCarthy, Brendan (Dance Books Ltd., Alton,Hampshire (UK), 2005)
PALABRAS CLAVE: Dance Screen Brighton, South East Dance, choreographer-directored films, dance and films, festival.